CLINICAL AND ANAMNESTIC FEATURES OF THE COURSE OF EXTRAGASTERAL MANIFESTATIONS OF HELICOBACTER PYLORI INFECTION IN GASTRODUODENAL PATHOLOGY IN CHILDREN - Khudayberganova N. Kh., Akhmedova I. M., Rakhmatullaeva G. K., Makhmudova M. S. (European Journal of Interdisciplinary Research and Development, 2023)
The article presents the results of a survey of 105 children with pathology of the gastroduodenal zone, which was mainly combined with the pathology of the biliary tract. The characteristic features of the anamnesis of these patients are given, the analysis of the diagnostic significance of various symptoms revealed by palpation of the anterior abdominal wall is carried out. The issues of verification of Helicobacter pylori infection using the respiratory Helic test, bacteriological and molecular genetic methods for the analysis of biopsy specimens of the duodenal mucosa and duodenal contents are considered. It has been proven that Helicobacter pylori is less common in children with isolated forms of chronic gastroduodenitis (CGD) and biliary tract dysfunction (BDBD), compared with children who have organic lesions of the biliary system in the form of chronic cholecystocholangitis, which requires verification of Helicobacter pylori in primary diagnosis -infection and subsequent etiotropic therapy.